Variabilidade interdecadal da precipitação na Amazonia Ocidental brasileira. - Souza, Reginaldo Luiz Fernandes de (2009)
The present work focused on the interdecadal variability of precipitation in the Western Brazilian Amazon in order to help improve this knowledge and, in addition, to analyze, study and evaluate the low-frequency variability of the hydrological cycle in this region. To this end, we used data collected from conventional rain gauge stations 5, available at the National Climatic Data Center (NCDC), reanalysis data of the following meteorological variables: long-wave radiation emerging (ROLE), temperature of the sea surface (SST) , vertical motion (Omega), zonal wind, as well as data series of the climate index of the Pacific Decadal Oscillation (ODP), and rainfall data of the project at the University of Delaware (UDEL), available at the Climate Diagnostic Center / National Oceanic and Atmospheric Administration (CDC / NOAA). Related to the local climate and the global level, particularly with the El Nino-Southern Oscillation (ENSO) and Pacific Decadal oscillation (ODP). It was noted that at the crucial stage of the ODP was a 8.1% increase in precipitation over the cold phase, mainly in the south-central axis of the western Amazon, while in the northwest basin of Rio Negro, it was noticed that at the hot rained 5.9% less when compared to the cold phase. Evidence indicates that since 1999, the ODP has entered into a new cold phase. Then, we analyzed the SST of the Pacific Ocean for the period 1999-2008 and observed the new configuration should last for 20 years, possibly causing significant changes in rainfall in this region.